Development of Colour Sorting Robotic Arm Using TCS3200 Sensor - Khairudin A.R.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Color; Object detection; Robotics; Color sensors; Color sorting; Condition; Energy; Human labor; Large volumes; Light intensity; Mechanical arm; Robotic implementation; Saves time; Robotic arms